Theoretical geochemistry : applications of quantum mechanics in the earth and mineral sciences - Tossell, John A.; Vaughan, David J., 1946- (Oxford ; New York : Oxford University Press, 1992)
This work is based on the observation that further major advances in geochemistry, particularly in understanding the rules that govern the ways in which elements come together to form minerals and rocks, will require the application of the theories of quantum mechanics. The book therefore outlines this theoretical background and discusses the models used to describe bonding in geochemical systems. It is the first book to describe and critically review the application of quantum mechanical theories to minerals and geochemical systems. The book consolidates valuable findings from chemistry and materials science as well as mineralogy and geochemistry, and the presentation has relevance to professionals in a wide range of disciplines. Experimental techniques are surveyed, but the emphasis is on applying theoretical tools to various groups of minerals: the oxides, silicates, carbonates, borates, and sulfides. Other topics dealt with in depth include structure, stereochemistry, bond strengths and stabilities of minerals, various physical properties, and the overall geochemical distribution of the elements.
Cover -- CONTENTS -- 146; INTRODUCTION -- 146;1 Historical perspective8212;ionic and atomistic approaches -- 146;2 Crystal45;field theory and the geochemistry of the transition metals -- 146;3 Quantum chemistry -- 146;4 Solid45;state quantum physics 40;band theory and related approaches41; -- 146;5 Quantum geochemistry -- 146;6 Models and methods -- EXPERIMENTAL METHODS -- 1 Diffraction effects -- 146;1 X45;ray diffraction -- 146;2 Neutron diffraction -- 146;3 Electron diffraction and associated phenomena -- 2 Electron and x45;ray spectroscopy -- 1 Photoelectron spectroscopy 40;and Auger electron spectroscopy41; -- 2 X45;ray emission spectroscopy -- 3 X45;ray absorption spectroscopy 40;including EXAFS and XANES41; -- 3 Optical 40;uv8211;visible8211;near45;ir41; spectroscopy -- 346;1 Electronic 40;optical41; absorption spectroscopy -- 346;2 Reflectance 40;diffuse and specular41; spectroscopy -- 4 Vibrational spectroscopy -- 446;1 Theoretical basis -- 446;2 Infrared spectroscopy -- 446;3 Raman spectroscopy -- 446;4 Reporting of data -- 5 Nuclear spectroscopy -- 546;1 Nuclear quadrupole resonance -- 546;2 Nuclear magnetic resonance -- 546;3 The Mssbauer effect -- 6 Other methods -- 646;1 Electron spin resonance -- 7 Concluding remarks -- 346; THEORETICAL METHODS -- 346;1 Elements of quantum mechanics -- 346;2 Details of Hartree8211;Fock8211;Roothaan calculations58; Choice of basis set -- 346;1 Minimum basis sets -- 346;2 Extended basis sets58; Double45;38;35;95059; bases -- 346;3 Extended basis sets58; Polarized bases -- 346;4 Extended basis sets58; Other approaches -- 346;5 Basis set and calculated properties -- 346;3 Improvements on the Hartree8211;Fock wave function -- 346;4 Dependence of computation time on basis45;set size 40;and property calculated41; for Hartree8211;Fock8211;Roothaan and configuration45;interaction calculations -- 346;5 Prediction of properties other than equilibrium geometries from Hartree8211;Fock8211;Roothaan calculations -- 346;6 Evaluation of spectral and other experimental parameters using Hartree8211;Fock8211;Roothaan calculations -- 346;7 Approximate Hartree8211;Fock methods -- 346;8 Hartree8211;Fock band45;structure calculations -- 346;9 Elements of density45;functional theory -- 346;10 The multiple45;scattering or scattered45;wave X45;38;35;94559; method -- 346;11 Density45;functional band theory -- 346;12 Theoretical ionic models8212;the modified electron45;gas approach -- 346;13 Simulation methods -- 346;14 Combined local45;density45;functional molecular dynamics approach -- 346;15 Relationships between localized and delocalized approaches -- 346;1546;1 Orbital and band energies -- 346;1546;2 Incorporation of external atoms of the solid into cluster calculations -- 346;16 Concluding remarks on different theoretical approaches -- 446; APPLICATION OF QUANTUM45;MECHANICAL METHODS TO SIMPLE INORGANIC 34;MOLECULES34; OF RELEVANCE TO MINERALOGY44; AND TO OXIDE M.
Includes bibliographical references and index.
Print version record.
WorldCat record variable field(s) change: 650
Keywords: Analytical geochemistry; Quantum chemistry; Mineralogical chemistry; Chemical bonds; Chemistry, Inorganic; Géochimie analytique; Chimie quantique; Chimie inorganique; inorganic chemistry; SCIENCE -- Earth Sciences -- Geography; SCIENCE -- Earth Sciences -- Geology; Analytical geochemistry; Chemical bonds; Mineralogical chemistry; Quantum chemistry; Electronic books